A relação igreja-mundo à luz da constituição pastoral Gaudium et spes. - Silva, Francisco Whalison da (2022)
Several transformations have been occurred in the society, involving, among other fields, the culture, economy, politics etc. This process of transformations has impacted also in the religious aspect, arousing interest by the Church-World relationship. During a long period, the Church was turned for interests and concernings ad intra, keeping an attitude of resistance or aversion and opposition to the modern world, that is, the ad extra reality. After the Pope João XXIII and the Second Vatican Council, begins a new stage in the life of the Church, maked by a live interest and concerning by the social changes, providing a better relationship between the Church and the society, between the doctrine and the modern times, between the catholic people and other christian. A privileged expression of this conciliar renewal process of the Church-World relationship is the Pastoral Constitution Gaudium et Spes. The current work has as general objective to analyze precisely the Church-World relationship from the Pastoral Constitution Gaudium et Spes about the Church in the modern world and to indicate, from the Pope Francisco, some current challenges of this question. The first chapter seeks to situate the Second Vatican Council on the context of the Church-World theme. After this, we intend to analyze the way how the Church-World relationship is understood and the terms in which it is formulated in the mentioned Constitution. Finally, we intend to think over its validity in the current historic context and over the new perspectives of the Church-World with the Pope Francisco leadership. This discussion helps us to understand how the Pastoral Constitution Gaudium et Spes opens the Church to dialogue with the Modern World, while, at the same time, it challenges us to update and deepen ourselves in this opening, dialogue and colaboration processes of the Church with the society.